2020
DOI: 10.1017/s0031182020001791
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D increases killing of intracellularLeishmania amazonensis in vitroindependently of macrophage oxidative mechanisms

Abstract: Vitamin D has been reported to activate macrophage microbicidal mechanisms by inducing the production of antimicrobial peptides and nitric oxide (NO), but conversely has been shown to contribute to a greater susceptibility to Leishmania amazonensis infection in mice. Thus, this study aimed to evaluate the role of vitamin D during intracellular infection with L. amazonensis by examining its effect on macrophage oxidative mechanisms and parasite survival in vitro. Vitamins D2 and D3 significantly inhibited proma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…On the other hand, VDR expression was associated with inhibition of the leishmanicidal activity of macrophages, as VDR-knockout mice showed greater resistance to infection by Leishmania major (Ehrchen et al, 2007). The incubation of macrophages with vitamin D reduced parasitic growth in the cells contaminated by Leishmania amazonenses (Machado et al, 2020), whereas mice treated every 48h for 12 weeks with calcitriol showed a drastic reduction in skin lesions caused by infection with Leishmania sp. (Ramos-Martínez et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, VDR expression was associated with inhibition of the leishmanicidal activity of macrophages, as VDR-knockout mice showed greater resistance to infection by Leishmania major (Ehrchen et al, 2007). The incubation of macrophages with vitamin D reduced parasitic growth in the cells contaminated by Leishmania amazonenses (Machado et al, 2020), whereas mice treated every 48h for 12 weeks with calcitriol showed a drastic reduction in skin lesions caused by infection with Leishmania sp. (Ramos-Martínez et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there has been no link among the status of vitamin D and the cell immune response to Leishmania. [84] Despite the major role of vitamin D in tissue healing, however, it had no discernible effect on the parasite's viability in individuals with active leishmaniasis [85]. Nitrous oxide (NO) is widely considered as the primary antimicrobial compound used to inhibit Leishmania major through Interferon-γ activated macrophages in the animal model.…”
Section: Role Of Vitamin Dmentioning
confidence: 99%
“…Endogenous calcitriol was also found to decrease the humoral IgE and IgG1 response to parasite infection [ 140 ]. Similarly, in the case of Leishmania amazonensis, vitamin D was shown to increase susceptibility to parasite infection in mice, but in an in vitro study, the reduction of parasite growth in infected macrophages in a process independent of macrophage oxidative mechanisms was demonstrated [ 141 ]. In the case of Plasmodium spp., vitamin D was found to inhibit parasite growth extensively during the acute phase and subsequent parasite growth, forming a mildly delayed peak [ 142 , 143 ].…”
Section: Melatonin and Lipid-soluble Vitamins In Toxoplasmosis Treatmentmentioning
confidence: 99%
“…It should be emphasized that high doses required to obtain positive immune effects in the host organism can result in severe side effects, including hypercalcemia [ 144 ]. Vitamin D deficiency was correlated with higher Toxoplasma infection prevalence, but the effects promoted by vitamin D in the immune system, including decreasing production of interleukin 12 (IL-12) and tumor necrosis factor-alpha (TNF-α) by monocytes and macrophages, and IFN-γ by CD4+ T cells, decreasing the differentiation of Th1 cells and increasing the differentiation of regulatory T cells, are unfavorable to the development of an effective immune response against the protozoan parasites [ 141 ]. Nevertheless, the in vitro studies revealed the potential of vitamin D in toxoplasmosis treatment.…”
Section: Melatonin and Lipid-soluble Vitamins In Toxoplasmosis Treatmentmentioning
confidence: 99%